The Influence of Self-Efficacy on Learning Outcomes in Economics Subjects in Class X IPS Students at SMA IT Al Bayyinah Pekanbaru - Rabi Atul Adawiya; Caska Caska; Gani Haryana (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to examine and explain the effect of self-efficacy on students’ learning outcomes. The background of this research is that students' learning outcome is still low. This research is included in the quantitative research. The population and sample in this study were all 84 students of grade X social studies at SMA IT Al Bayyinah Pekanbaru. Sampling technique with saturation sampling. Data collection techniques used are documentation and questionnaires. The classic assumption test includes the normality test, linearity test and multicollinearity test. Data analysis technique with simple linear regression.